Malaysian armed force the nation shield : 80th anniversary (Malaysian Armed Forces Headquarters, 2013)
This is a book about the Malaysian Armed Forces. This book is about who they are and what they do to answer the call of duty. This book has been written for the general public and contain a wealth of information for anyone who want to know more about the Malaysian Armed Forces. This book is gleaned from current information regarding the Army, Navy and Air Force with a sense of optimism, that the book proves helpful to many who are new or searching for more insights regarding the Malaysian Armed Forces.